Safeguarding cultural heritage from climate change related hydrometeorological hazards in Central Europe. (September 2021) - Bonazza, Alessandra; Sardella, Alessandro; Kaiser, Anna; Cacciotti, Riccardo; De Nuntiis, Paola; Hanus, Christian; Maxwell, Ingval; Drdácký, Tomas; Drdácký, Milos
Abstract: This paper presents a method for contributing to risk assessment of cultural heritage exposed to hydrometeorological extreme events linked to climate change. The methodology adopted involves the development of hazard maps at territorial level, based on outputs from climate models, and the vulnerability assessment at building scale, underlying on physical and managerial criticalities of built heritage. Results are discussed for two pilot sites highly susceptible to flooding impacting large areas: Prague - Troja (CZ) and Krems - Stein (AT). Outcomes include climate projections of changes of the extreme precipitation index R5xday with spatial resolution of ∼12 km for the near and far future (2021–2050; 2071–2100), under two different scenarios (stabilizing and pessimistic). A general increase of Rx5day in the investigated areas in the far future under the pessimistic scenario is foreseen, highlighting a high likelihood of flooding risk. Furthermore, it is determined that the buildings selected in the pilot areas present a high degree of vulnerability, mainly due to a lack of a maintenance plan and a significant susceptibility of the structures to water impact. Therefore preparedness turns out to be a crucial step in the management of the sites for enhancing their resilience to calamitous events.